Clinical implications of delayed orthostatic hypotension: A 10-year follow-up study. (20th October 2015) - Gibbons, Christopher H.; Freeman, Roy
Abstract : Objective: To define the long-term outcome of delayed orthostatic hypotension (OH). Hypothesis: Delayed OH is an early and milder form of OH that progresses over time. Methods: We reviewed the medical records of 230 previously reported patients who completed autonomic testing at our center from January 1, 2002, through December 31, 2003. All available information on clinical diagnosis, mortality, medication use, and autonomic testing were extracted and included in the reported outcomes. Standard criteria were used to define OH and delayed OH. Results: Forty-eight individuals with delayed OH, 42 individuals with OH, and 75 controls had complete follow-up data. Fifty-four percent of individuals with delayed OH progressed to OH. Thirty-one percent of individuals with delayed OH developed an α-synucleinopathy. The 10-year mortality rate in individuals with delayed OH was 29%, in individuals with baseline OH was 64%, and in controls was 9%. The 10-year mortality of individuals who progressed to OH was 50%. Progression to OH was associated with developing an α-synucleinopathy, baseline diabetes, and abnormal baseline autonomic test results. Conclusion: Delayed OH frequently progresses to OH with a high associated mortality.